THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN ENGLISH TEACHING AT SMAN 1 BUNGA RAYA IN SIAK - Gunawan, Heri; Afrianto, Afrianto; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed at investigating the implementation of Scientific Approach by English teachers of one senior high school in Siak Regency. The study is specifically aimed at investigating how the scientific approach is implemented in the classroom and identifying the problems faced by the teachers during the implementation. The researcher selected three teachers of SMAN 1 Bunga Raya Siak as the participants using total sampling method. This study employed mixed method, combining quantitative and qualitative methods of data collection. The quantitative data were collected from a survey while the qualitative ones were obtained through semi-structured interviews. The combination of the two types of data was deliberately chosen for the researcher intended to understand the depth of the data. The findings showed that the teachers have implemented the scientific approach relatively well. This can be seen from the results of the survey in which the overall mean score calculated was 4.4 and categorized ‘very good’. However, the occurrence of some problems in the implementation was inevitable. In general, the problems can be classified into four: (a) insufficient English teaching hour; (b) the students’ high diversity in terms of ability; (c) discrepancy between curriculum and national examination contents; and (d) lack of the school’s and students’ facility.Keywords: Scientific Approach, implementation, English teaching, Siak Regency